Crystal growth of a MnS buffer layer for non-polar AlN on Si (100) deposited by radio frequency magnetron sputtering. (22nd February 2019) - Tatejima, Kota; Nagata, Takahiro; Ishibashi, Keiji; Takahashi, Kenichiro; Suzuki, Setsu; Ogura, Atsushi; Chikyow, Toyohiro
Abstract: The growth conditions of MnS thin film on a Si (100) substrate deposited by the RF-magnetron sputtering method were investigated. The MnS is a buffer layer for the epitaxial growth of non-polar AlN thin film on the Si (100) substrate. The 4°-off-Si (100) substrate and the insertion of MnS film grown at room temperature (RT-MnS) improved the crystallinity and the surface roughness of the MnS film. In particular, the 20 nm thick RT-MnS showed a reduction of surface roughness of the MnS layer deposited at 550 °C. The root mean square value of the MnS layer was 0.23 nm, which is in the same range as that of the Si substrate. X-ray photoelectron spectroscopy measurements revealed that RT-MnS insertion with a thickness over 10 nm reduced the sulfur vacancy formation in the MnS film deposited on RT-MnS, and the MnS was thermally stable at the growth temperature of AlN.